Diagnostic Accuracy of Endoscopic Ultrasound-Guided Fine-Needle Aspiration Cytology, Carcinoembryonic Antigen, and Amylase in Intraductal Papillary Mucinous Neoplasm. Issue 6 (July 2016) - Moris, Maria; Raimondo, Massimo; Woodward, Timothy A.; Skinner, Verna; Arcidiacono, Paolo G.; Petrone, Maria C.; De Angelis, Claudio; Manfrè, Selene; Fusaroli, Pietro; Asbun, Horacio; Stauffer, John; Wallace, Michael B.
Abstract : Objectives: The aim of this study was to determine the accuracy of cytology, carcinoembryonic antigen (CEA), and amylase levels in the preoperative diagnosis of intraductal papillary mucinous neoplasms (IPMNs). Methods: An international registry was started in 2005 and included patients with clinically suspected IPMNs. Those who underwent surgery and had preoperative endoscopic ultrasonography fine-needle aspiration were selected for the study. Results: One hundred eighty patients were included. Cytological analysis for neoplastic cells in IPMNs showed high specificity (87.8%) but low sensitivity (39.4%). The median CEA level was 525.5 ng/mL (n = 78) in IPMNs versus 9.7 ng/mL in nonmucinous cysts (n = 6), showing an area under the receiver operating characteristic curve (AUC) of 0.87. The optimal cutoff CEA value for distinguishing IPMN from nonmucinous cysts was 129 ng/mL. At this level, the sensitivity was 76.9%, and specificity was 83.3%, yielding a positive predictive value of 95.9% and a negative predictive value of 41.9%. Carcinoembryonic antigen was a poor predictor of neoplasia in IPMNs (AUC = 0.55). Amylase did not distinguish IPMNs from mucinous cystadenomas (MCAs) (median, 3759 U/L [n = 28 IPMNs] and 497 U/L [n = 3 MCAs], AUC = 0.65). Conclusions: Cytology has a limited role because of its lack of sensitivity. Carcinoembryonic antigen modestly differentiated between mucinous and nonmucinous lesions. Amylase did not distinguish IPMNs versus MCAs. Abstract : Supplemental digital content is available in the text.